Organotropism of persistent organic pollutants and heavy metals in the Greenland shark Somniosus microcephalus in NE Greenland - CORSOLINI, SIMONETTA; ANCORA, STEFANIA; BIANCHI, NICOLA; Mariotti, G.; LEONZIO, CLAUDIO; Christiansen, J. S. (Marine Pollution Bulletin, 2014)
The Greenland shark Somniosus microcephalus is an opportunistic feeder, a top predator, and a very long-lived species. The brain, liver, red and white muscle, gonads, fat, skin, pancreas, and spleen of Greenland sharks from NE Greenland fiords were analysed for PCBs, PCDDs/DFs, PBDEs; DDT isomers; HCH isomers; dieldrin; endrin; HCB; Cd, Hg, Pb, and Se. PCBs (2.01-103 ng/g wet wt) and PBDEs (7.9-3050 pg/g wet wt) were detected in most of the samples. PCDDs/DFs showed high values when detected. DDTs, HCB and HCHs were only detected in some tissues. The Sigma TEQ was 5.76 pg/g in muscle. Cadmium mainly accumulated in the pancreas and liver (19.6 and 10.7 mg/kg dry wt, respectively); mercury in red muscle (4.10-6.91 mg/kg dry wt); selenium in the pancreas (3.57 mg/kg dry wt) and spleen (1.95 mg/kg dry wt); lead in the skin (0.358 mg/kg dry wt). The selenium-mercury ratio in the liver was also evaluated.